1987
DOI: 10.1128/iai.55.3.555-558.1987
|View full text |Cite
|
Sign up to set email alerts
|

F41 pili as protective antigens of enterotoxigenic Escherichia coli that produce F41, K99, or both pilus antigens

Abstract: Pigs suckling dams that have been vaccinated with pilus antigen are protected against challenge with enterotoxigenic Escherichia coli (ETEC) strains that express the same pilus antigen. However, some ETEC strains express more than one pilus antigen. Pregnant swine were vaccinated either with E. coli HB101 that harbored a recombinant plasmid coding for F41 expression (F41+) or with the HB101 parent strain that carries the pHC79 vector (F41-). Suckling pigs born to vaccinated dams were challenged with ETEC that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Our finding that vaccination of dams with the F5 antigen can protect their offspring against challenge with an E. coli strain that expresses both F5 and F41 confirms earlier work in both pigs (Morgan et al., 1978) and cattle (Acres et al., 1979). Conversely, it has been shown that vaccination with a vaccine containing F41 only will not protect against an E. coli strain expressing both F5 and F41 (Runnel et al., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that vaccination of dams with the F5 antigen can protect their offspring against challenge with an E. coli strain that expresses both F5 and F41 confirms earlier work in both pigs (Morgan et al., 1978) and cattle (Acres et al., 1979). Conversely, it has been shown that vaccination with a vaccine containing F41 only will not protect against an E. coli strain expressing both F5 and F41 (Runnel et al., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The following methods are in use: 1. Vaccination against bacterial adhesion factors (Levine et al, 1983;Runnels et al, 1987). 2.…”
Section: Discussionmentioning
confidence: 99%
“…in sealed tubes, stored at room temperature in the dark, with a nonselective transfer (without cloning or selection) to fresh medium every 3 years. All inocula came from samples of the same culture, which was prepared and stored at -70°C, as reported previously (12,19), for more than 1 year. Samples were thawed and diluted in Trypticase soy broth (BBL) just before inoculation into pigs.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment in suckling pigs involved the newborn pigs of five gilts (primiparous swine). In a separate study (19), four of these gilts received a vaccine containing F41 fimbriae, and the other received a placebo. None of them was vaccinated against K99.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation